Assessing perceptions of stigmatization by others for seeking help in China: psychometric characteristics and measurement invariance across gender and therapy experience - Cheng, Kun; Yang, Wenxian; Zhang, Yan-Hong; She, Zhuang (Frontiers in Psychology, 2024)
The stigma of social networks may be more noticeable in collectivist societies like China, but research in this area has largely been overlooked due to a lack of reliable measurement. To address this gap, this study tested the psychometric properties of the Chinese version of the Perceptions of Stigmatization by Others for Seeking Help (PSOSH) scale in the Chinese general population, and tested its invariance across gender and prior therapy experience. In a national online survey, 640 adults completed the PSOSH and conceptually related scales: Self-stigma of Seeking Help (SSOSH), Stigma of Seeking Professional Psychological Help Scale (SSPPH, i.e., public stigma) and Attitudes toward Seeking Professional Psychological Help Scale-Short Form (ATSPPH-SF). Confirmatory factor analysis supported the unidimensional structure of the original PSOSH. The Cronbach's α coefficient was .84 and the 3-week test-retest reliability of was .77. The PSOSH showed moderate correlations with the three conceptually related scales, supporting its concurrent validity. Importantly, the PSOSH significantly predicted self-stigma scores, even when considering demographic variables and public stigma, supporting its incremental validity. The scale also demonstrated scalar invariance across gender and across subgroups who had vs. did not have previous therapy experience, supporting comparisons of latent means across these groups. The PSOSH is a reliable and valid instrument for assessing social network stigmatization of professional help-seeking in Chinese community samples.